Intervensi Keperawatan Holistik Melalui Terapi Musik untuk Meningkatkan Kualitas Tidur Pasien Insomnia - Rovina Efranti Br Barus; Rika Endah Nurhidayah (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2023)
Insomnia is a sleep disorder that often occurs and has a complex effect on human health. In addition to causing difficulties for patients in carrying out daily activities, insomnia also causes serious mental and physical health problems. Therefore, there is a need for methods that can overcome this. Some literature states that music therapy methods can improve sleep quality so that insomnia disorders can be overcome. The purpose of this study was to identify and evaluate the effect of music therapy interventions on sleep quality in patients with insomnia. The method used is Systematic Review using the ScienceDirect database, Wiley Online, Springer Link, and Taylor & Francis Online. The selection of articles used the Preferred Items for Systematic Reviews and Meta-Analyses (PRISMA) method which found 10 articles that matched the inclusion criteria. Research results show that music therapy has a significant effect on improving sleep quality in people with insomnia